An Algorithm to Evaluate Suspected Lung Metastases in Patients with HPV‐Associated Oropharyngeal Cancer. (26th September 2017) - VanKoevering, Kyle K.; Marchiano, Emily; Walline, Heather M.; Carey, Thomas E.; McHugh, Jonathan B.; Brenner, J.Chad; Goudsmit, Christine M.; Belille, Emily; Spector, Matthew E.; Shuman, Andrew G.; ,
Abstract : Distinguishing between distantly metastatic and metachronous lung primary carcinoma is challenging for patients with a history of head and neck cancer. There are implications for registry data, prognosis and related counseling, and management options, including eligibility for precision oncology trials. Patients with human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma who were treated under a uniform clinical protocol and achieved a complete response were identified in a single‐institution prospective head and neck cancer epidemiology database (n = 205). Fifteen patients presented with pulmonary nodule(s) after completion of therapy. We describe our algorithm for the evaluation of these patients, including histopathology, p16 immunohistochemistry, and HPV in situ hybridization.